Biological activities and phytochemical characterization of Sideritis germanicopolitana subsp. viridis and S. libanotica subsp. linearis extracts and extract-loaded nanoparticles - Taşkın, Turgut; Yılmaz, Beyza Nur; Hasan Niari Niar, Shalaleh; Ermanoğlu, Mizgin; Taşkın, Duygu; Şenkardeş, İsmail; Şahin, Talip; Çalışkan Salihi, Elif; Sezer, Ali Demir; Kerimoğlu, Oya; Elçioğlu, Hatice Kübra (Frontiers in Pharmacology, 2025)
IntroductionThe current study focuses on evaluating the biological activity and analysis of phytochemical content of extracts and extract-loaded nanoparticles from Sideritis germanicopolitana subsp. viridis (endemic, SGV) and S. libanotica subsp. linearis (SLL).MethodsAntioxidant activities of extracts and nanoparticles were investigated by DPPH, FRAP and CUPRAC methods. Enzyme inhibition potentials of extracts and nanoparticles were evaluated by Ellman and indophenol methods. Phytochemical contents were analyzed by HPLC-DAD. Plant extracts were encapsulated by the ionic gelation method which was modified in our laboratory using the green chemistry approach.Results and DiscussionIt was found that the 70% ethanol extracts of SGV and SLL exhibited the highest antioxidant activity in terms of DPPH, FRAP and CUPRAC compared to other extracts. The findings showed that both 70% ethanol extract-loaded nanoparticles obtained from SGV and SLL showed lower DPPH radical scavenging, iron (III) reducing and copper (II) reducing activities compared to crude extracts. It was determined that the 70% extracts of SGV and SLL exhibited a higher potential to inhibit the enzyme urease than other extracts. The anti-urease activity of the nanoparticle loaded with SLL 70% ethanol extract was found to be greater than that of the nanoparticle made with SGV 70% ethanol extract. Furthermore, an analysis of the acetylcholinesterase enzyme inhibition capacity of various extracts from both plants revealed that the 70% ethanol extracts of each plant species had a greater potential for enzyme inhibition than the other extracts. The anticholinesterase activity of the nanoparticle loaded with SLL 70% extract was found to be higher than that of the nanoparticle loaded with SGV 70% ethanol extract. In this study the phenolic metabolites were examined, luteolin (27.44 μg/mg extract) and p-coumaric acid (20.03 μg/mg extract) were found at the highest concentration in the SGV plant while rosmarinic acid (8.70 μg/mg extract), caffeic acid (6.46 μg/mg extract) and p-coumaric acid (4.42 μg/mg extract) were found at the highest concentration in the SLL plant. However, the data demonstrated that the nanoparticles had lesser biological activity potential than crude extracts.ConclusionThe substantial biological activities of the nanoparticles developed as a result of this work showed that these formulations are suitable for use as antioxidant, anti-urease and anticholinesterase medicines in the future due to the benefits of using nanoparticles in the therapeutics such as the controlled release of the active agents and the diminished side effects.